2016
DOI: 10.1371/journal.pone.0167459
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Setting the Standards of Health Promoting Hospitals on Hospital Indicators in Iran

Abstract: Hospitals play a critical role in the health promotion of the society. This study aimed to determine the impact of establishing standards of health promoting hospitals on hospital indicators in Shahroud. This applied study was a quasi-experimental one which was conducted in 2013. Standards of health promoting hospitals were established as an intervention procedure in the Fatemiyeh hospital. Parameters of health promoting hospitals were compared in intervention and control hospitals before and after of interven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 17 publications
0
8
0
2
Order By: Relevance
“…The most prominent differences between the iHPHs and non-iHPHs were found in Standards 1 (policy and leadership) and 5 (implementation and monitoring). A study in Iran has found a similar pattern of differences [55]. Standards 1 and 5 are related to the essential organizational capacity for HPH.…”
Section: Discussionmentioning
confidence: 79%
“…The most prominent differences between the iHPHs and non-iHPHs were found in Standards 1 (policy and leadership) and 5 (implementation and monitoring). A study in Iran has found a similar pattern of differences [55]. Standards 1 and 5 are related to the essential organizational capacity for HPH.…”
Section: Discussionmentioning
confidence: 79%
“…The highest achievement indicators are in the indicator "Hospital mandates staffs to implement Islamic values in empowering the community while serving in curative, rehabilitative, preventive, and promotive aspects" for RSIJ Sukapura, but the indicator "Hospital mandates hospital staff to empower the community while serving in curative, rehabilitative, preventive, and promotive aspects is still a low average level of achievement (49.3%). Important hospital community empowerment is assessed/ measured because both nationally and globally, HPH is expressed as "expanding the hospital's public health role", in relation to local communities and their social and health services which will optimize networking among providers, users and community leaders in the health sector and society as a whole (Amiri et al, 2016;Whitehead, 2005). In the course of the HPH partnership in RSM, empowerment of the community and RSM target groups related to national and local health priority issues in the RSM region became the main objective of HPH implementation both inside and outside the building.…”
Section: Methodsmentioning
confidence: 99%
“…Penelitian pertama dilakukan oleh Amiri (2016), dimana mereka menunjukkan bahwa terdapat hubungan yang signifikan antara kepuasan pasien dengan penerapan standar promosi kesehatan (P = 0,001). Selain itu, terdapat perbedaan yang signifikan antara rerata edukasi kesehatan yang dilakukan kepada pasien sebelum dan setelah penetapan standar PKRS (P = 0,001), dimana kepuasan pasien lebih baik setelah penerapan standar promosi kesehatan RS (10). Penelitian kedua dilakukan oleh Wartiningsih (2020).…”
Section: Gambar 1 Diagram Alir Pencarian Artikelunclassified
“…Rumah sakit berperan aktif dalam memberikan pelayanan yang komprehensif dan diwujudkan melalui promosi kesehatan, pencegahan, pengobatan, dan rehabilitasi penyakit. Banyak kesulitan yang terkait dengan pengembangan kesadaran akan kesehatan dan penyakit terkait, sehingga PKRS mendorong pasien dan keluarga untuk terlibat aktif dalam perencanaan program promosi kesehatan sebagai bagian yang tidak terpisah dari pelayanan di RS (10,14).…”
Section: Pembahasanunclassified